Pengaruh Inovasi Produk dan Pengunjung Showroom Mobil Hyundai Terhadap Penjualan di PT.Hyundai Mobil Indonesia (HMI) Cabang Soekarno Hatta Bandung - Asep Purnama (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This study aims to find out how the contribution of product innovation (X1) and showroom visitors (X2) to sales growth (Y) at PT.Hyundai Mobil Indonesia Soekarno Hatta Bandung branch. From 2013 to 2022, the sample population consists of all showroom visitors who have an interest in the products being sold. The information used in this check is optional. By using secondary data, the author's quantitative research method uses the normality test, multicollinearity test, heteroscedasticity test, partial test (t), simultaneous test (f), and test of the coefficient of determination (R2). Research shows that product innovation has a modest but positive effect on sales. Showroom visitors have a significant and positive effect on sales. Sales are heavily influenced by product innovation and showroom visitors. Key words: Product Innovation, Showroom Visitors, Sales